PERBAIKAN TATA LETAK DAN MATERIAL HANDLING LANTAI PRODUKSI PT. HAMSON INDONESIA UNTUK MENCAPAI TARGET PRODUKSI DENGAN MENGGUNAKAN METODE PAIRWISE EXCHANGE DAN SIMULASI - Sucipto Adisuwiryo; Parwadi Moengin; Yudhistira Lionel (JURNAL TEKNIK INDUSTRI, 2014)
PT. Hamson Indonesia is a national company that manufactures dredger and its components.The problems that arise on the production floor is the production target is not achieved at thespecified time. This problem is caused by the layout of the production floor is irregular and also theuse of material handling is not optimal. Average production Winches, Cutter, and Steering Gearproduced today are each 1 unit in 42.33 hours while the production target set is 1 unit in 40 hours.The first methodology used is criteria of layout, material handling checklist and applicationtype layout. Criteria layout and material handling checklist is used as an analysis of the condition ofthe layout and material handling this time on the production floor and also to identify the cause offailure to achieve production targets. The application type layout is one approach to implement thetype of layout in accordance with the conditions of production floor layout in PT. Hamson Indonesia.Then evaluate the layout and material handling system using pairwise exchange method andsimulation in order to get the design layout and material handling systems are best in order toachieve production targets.It can be concluded that the issues affecting the achievement of production targets are notlaying irregular departments and the use of material handling equipment that is not optimal, so itneeds a revision of the layout and material handling systems. Application of an appropriate type oflayout is the process layout. Then evaluate the layout by using the pairwise exchange method with theresults of the exchange of 3 and 4 departments namely milling machines and drilling machines. Thenew layout of the data results of these evaluations are used as a model to be re-evaluated by usingsimulation method in order to meet the production target which is completed within 40 hours. Thereare 3 models of the proposed model first proposed by replacing the manual material handling withtrolley, the proposed model 2 with the addition of 1 machine cutting and 1 drilling machine , and 3with the incorporation of the 2 models previously proposed. Proposed model 3 is the best model thatrequires a minimum production time which is 38 hours 57 minutes.